2023
DOI: 10.11124/jbies-22-00261
|View full text |Cite
|
Sign up to set email alerts
|

Patient involvement interventions for patients with kidney failure making end-of-life care decisions: a scoping review

Abstract: Objective: The objective of this review was to investigate and map empirical evidence of patient involvement interventions to support patients with kidney failure making end-of-life care decisions in kidney services. Introduction: Clinical guidance integrating end-of-life care within kidney failure management pathways varies. Advance care planning interventions aimed at involving patients with kidney failure in their end-of-life care planning are establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 68 publications
(554 reference statements)
1
5
0
Order By: Relevance
“…This study aimed to describe the development process of the DESIRE intervention. From investigating users' needs, goals, strengths, limitations, context and intuitive processes we had some idea about which components the intervention should contain (Buur et al, 2024;Buur, Bekker, Madsen, et al, 2023;Buur, Bekker, Mathiesen, et al, 2023), (Karlsson et al, 2023) found several enablers and outcomes from involving relevant stakeholders that were similar to our findings. They found that the researchers' perspective was changed based on the experiences of the patients and relative partners, who had provided the researchers with new knowledge from their specific stakeholder perspectives (Karlsson et al, 2023).…”
Section: Strengths and Limitations Of The Worksupporting
confidence: 68%
See 4 more Smart Citations
“…This study aimed to describe the development process of the DESIRE intervention. From investigating users' needs, goals, strengths, limitations, context and intuitive processes we had some idea about which components the intervention should contain (Buur et al, 2024;Buur, Bekker, Madsen, et al, 2023;Buur, Bekker, Mathiesen, et al, 2023), (Karlsson et al, 2023) found several enablers and outcomes from involving relevant stakeholders that were similar to our findings. They found that the researchers' perspective was changed based on the experiences of the patients and relative partners, who had provided the researchers with new knowledge from their specific stakeholder perspectives (Karlsson et al, 2023).…”
Section: Strengths and Limitations Of The Worksupporting
confidence: 68%
“…These were part of the workshop considerations and discussions. In addition, key uncertainties that had been identified prior to the development process (Buur et al, 2024;Buur, Bekker, Madsen, et al, 2023;Buur, Bekker, Mathiesen, et al, 2023) were covered in the workshop discussions, for example, the duration of the SDM conversations and at what point in the illness trajectory a conversation should be offered to patients with kidney failure and their relatives.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations